Nurazyyati receives Professor Dato’ Dr. Mashitah Mohd Yusoff Award - Siti Nur Azwin, Zulkapri (2022)
PAYA BESAR, 6 November 2022 - The world was shocked by the COVID-19 pandemic that affected health and finances and claimed many lives.